Trace scandium regulated corrosion-resistant aluminum-magnesium alloy and preparation method thereof

CN122959583APending Publication Date: 2026-10-23DALISHEN ALUMINUM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610949848.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]为了解决上述技术问题,本发明提供一种微量钪调控耐腐蚀铝镁合金及其制备方法,旨在解决现有铝镁合金晶间腐蚀严重、强度与耐蚀性难以兼顾、钪元素工业化添加稳定性差的弊端,其通过精准配比微量钪和辅助微量元素复合改性,搭配专用熔铸、轧制、分级热处理工艺,破碎网状β相、细化基体晶粒、析出弥散Al3Sc强化相,同步大幅提升合金力学强度、晶间耐蚀性能,实现低成本规模化工业量产

Benefits of technology

[0014]与现有技术相比,本发明可以获得包括以下技术效果:1.本发明采用Sc-Zr-Mn-Cr复合微合金化,微量钪即可实现晶粒细化+网状β相改性双重作用,解决传统单一Sc改性成本高、耐蚀提升有限的缺陷;2. 铝液降温后再加入Al-Sc、Al-Zr中间合金,避免高温下Sc、Zr形成粗大初生金属间化合物,配合低速搅拌、精准铸锭冷却速率,解决工业化铸锭元素偏析难题;3.采用梯度多道次轧制工艺,高温热轧+中间去应力退火+适度冷轧,逐级调控变形储能,配合纳米析出相细晶作用,稳定将晶粒尺寸控制在50μm以内,兼顾板材成形塑性与力学性能;4.分级热处理,避免传统长时间高温时效导致晶界连续网状β相,仅析出离散点状β相,切断晶间腐蚀连续通道,显著降低晶间腐蚀、剥落腐蚀敏感性;5.成品合金同时满足高力学性能与海洋严苛耐腐蚀要求,填补改性铝镁合金成套工业化技术空白,可直接用于海洋船舶甲板、航空轻量化结构件、沿海风电装备,盐雾、海水工况服役寿命提升2倍以上,生产流程兼容现有铝加工产线,具备规模化工业化价值。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application belongs to the technical field of aluminum alloy material, and particularly relates to a trace scandium regulated corrosion-resistant aluminum magnesium alloy, which comprises the following components in percentage by mass: Mg: 4.8-5.6%, Sc: 0.08-0.15%, Mn: 0.3-0.5%, Zr: 0.05-0.10%, Cr: 0.02-0.04%, Ti: 0.01-0.03%, Fe≤0.12%, Si≤0.10%, and the balance of Al and inevitable trace impurities. The present application solves the intergranular corrosion and spalling corrosion defects of the traditional aluminum magnesium alloy from the microstructure source, simultaneously accurately controls the trace scandium addition interval, cooperates with a special melting and casting process to improve the scandium yield, the alloy tensile strength is greater than or equal to 400 MPa, the intergranular corrosion depth is less than or equal to 50 microns, the spalling corrosion reaches EA-EB level, the whole process is adapted to the existing aluminum processing production line, can be mass-produced, and is suitable for marine ships, aerospace, coastal wind power corrosion-resistant lightweight structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy material technology, and particularly relates to a micro-scandium-regulated corrosion-resistant aluminum-magnesium alloy and its preparation method. Background Technology

[0002] 5A72 series Al-Mg alloys are widely used in shipbuilding, aerospace vehicles, and marine equipment structural components due to their low density, high specific strength, and good formability. However, conventional 5A72 alloys have a high magnesium content, which makes them prone to precipitating a continuous network of β-(Al3Mg2) phase during solidification and service. This phase has an electrode potential much lower than that of the aluminum matrix, making it highly susceptible to intergranular corrosion and exfoliation corrosion under seawater and high-humidity salt spray conditions, significantly shortening the service life of components.

[0003] Current research on Al-Sc alloys, both domestically and internationally, shows that scandium can refine aluminum grains and induce Al3Sc nano-precipitates to inhibit recrystallization, leading to the mass application of corrosion-resistant Sc aluminum alloys in marine and aerospace applications. Universities such as Central South University and Northeastern University have conducted related mechanism studies, but existing technologies suffer from three major shortcomings: 1. Poor uniformity of trace Sc addition results in low Sc yield in the melt, making large-scale casting prone to compositional segregation; 2. Adding Sc alone cannot completely block continuous β-phase precipitation, resulting in excessive intergranular corrosion depth; 3. The rolling and heat treatment processes are not matched to the grain-refining properties of Sc, making it difficult to synergistically improve material strength and corrosion resistance, and simultaneously achieve a balance between grain refinement, strength enhancement, and corrosion resistance.

[0004] Existing technologies disclose Sc / Zr modified Al-Mg alloys, but most of them are limited to laboratory small ingot research. They lack complete sets of processes adapted for industrial semi-continuous casting, gradient rolling, and staged heat treatment. Furthermore, they do not strictly limit the Sc / Zr ratio and smelting and feeding temperature, making it impossible to stably control the size of nano-Al3(Sc,Zr) and the discrete point distribution of the β phase. This easily leads to problems such as coarse primary ScZr phases, network β precipitation, excessively large grain size, and severe intergranular corrosion, which limits the large-scale application of high-Mg aluminum alloys under harsh corrosive conditions. Publication No. CN104694801A discloses an aluminum-magnesium-scandium-zirconium aluminum alloy plate and its manufacturing method. The Mg content is 5.5-6.5%, the Sc content is as high as 0.2-0.4%, the scandium cost is high, and it adopts a traditional single rolling process without intermediate stress relief annealing process, only simple aging treatment, lacking high temperature water quenching solidification step, which easily forms a continuous network β-(Al3Mg2) phase at the grain boundary, resulting in poor exfoliation corrosion resistance. It is only suitable for lightweight aerospace applications, but not for long-term corrosion-resistant marine applications. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a trace scandium-modified corrosion-resistant aluminum-magnesium alloy and its preparation method. It aims to overcome the shortcomings of existing aluminum-magnesium alloys, such as severe intergranular corrosion, difficulty in achieving both strength and corrosion resistance, and poor stability of industrially added scandium. By precisely proportioning trace scandium and auxiliary trace elements for composite modification, combined with specialized casting, rolling, and graded heat treatment processes, the invention breaks down the network β phase, refines the matrix grains, and precipitates dispersed Al3Sc reinforcing phases, simultaneously and significantly improving the alloy's mechanical strength and intergranular corrosion resistance, thus achieving low-cost, large-scale industrial production.

[0006] This invention provides a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, comprising the following components by mass percentage: Mg: 4.8–5.6%, Sc: 0.08–0.15%, Mn: 0.3–0.5%, Zr: 0.05–0.10%, Cr: 0.02–0.04%, Ti: 0.01–0.03%, Fe ≤ 0.12%, Si ≤ 0.10%, with the balance being Al and unavoidable trace impurities, totaling ≤ 0.1% impurities. This invention strictly limits the impurity elements (Fe ≤ 0.12%, Si ≤ 0.10%), ensuring corrosion resistance from the source.

[0007] A further improvement of this invention is that the mass ratio of Sc to Zr is controlled at (1.2–2.0):1, resulting in the formation of a thermally stable Al3(Sc,Zr) composite nanoprecipitate within the alloy. This specific ratio aims to generate a highly thermally stable Al3(Sc,Zr) composite nanoprecipitate. The addition of trace amounts of scandium (0.08–0.15%) refines the grains and alters the precipitation morphology of the corrosion phase.

[0008] A further improvement of the present invention is that the finished aluminum alloy has a tensile strength ≥400MPa, a yield strength ≥250MPa, an elongation after fracture ≥10%, and corrosion resistance that meets the requirement of intergranular corrosion depth ≤50μm and exfoliation corrosion level reaching EA~EB grade.

[0009] A further improvement of the present invention is that the aluminum alloy is used in marine ship structural components, lightweight load-bearing components for aerospace, and corrosion-resistant plates for coastal wind power equipment.

[0010] This invention also provides a method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, specifically including the following steps: (1) Smelting: After preheating the pure aluminum ingot to 720°C, put it into the smelting furnace and heat it to 750-760°C to completely melt it into aluminum liquid. Then, add Mg ingot, Al-Mn master alloy, Al-Cr master alloy and Al-Ti master alloy in sequence, stir and mix thoroughly, then adjust the temperature of the aluminum liquid to 700-730°C, add Al-Sc and Al-Zr master alloy, stir at low speed electromagnetically for 20-30 min, and keep it at the temperature for 25-35 min. (2) Casting: Semi-continuous casting is adopted, with online argon rotary degassing and ceramic foam filtration purification in the furnace. The cooling rate of the semi-continuous casting is controlled at 2.2~2.8℃ / s, and the casting speed is 60mm / min~80mm / min, to obtain a non-segregated alloy ingot. (3) Homogenization annealing: The cast ingot is kept at 430-450℃ for 10-14 hours and then air-cooled to room temperature; (4) Hot rolling: The homogenized ingot is subjected to multiple reciprocating hot rolling processes, and the deformation is gradually reduced. The initial rolling temperature is 410-430℃, the single-pass reduction is 12%-18%, and the total hot rolling reduction is 75%-80%. The hot-rolled plate is obtained by rolling. (5) Intermediate stress-relief annealing: The obtained hot-rolled plate is kept at 350-370℃ for 1.5-2.5h; (6) Cold rolling: The hot-rolled sheet is cold rolled at room temperature, and the total deformation of the cold rolling is controlled at 30% to 35% to obtain aluminum alloy sheet with a thickness of 1.5 to 12 mm. (7) Graded heat treatment: The obtained aluminum alloy plates are subjected to solution quenching and low temperature aging treatment in sequence.

[0011] A further improvement of the present invention is that: in the solution quenching treatment, the cold-rolled sheet is placed in a solution furnace, the temperature is set at 460-470℃, the holding time is 80-100min, and water quenching is performed immediately after the holding time is completed, with an overall cooling rate ≥100℃ / s, so that the alloy strengthening elements are fully dissolved.

[0012] A further improvement of the present invention is that: the low-temperature aging treatment involves aging the quenched plate at a temperature of 310-330°C for 5-7 hours, followed by natural air cooling to room temperature, which yields the finished aluminum alloy plate.

[0013] A further improvement of the present invention is that, after solution treatment and aging, the size of the Al3(Sc,Zr) precipitates inside the alloy is controlled at 5-25 nm, the average grain size of the plate is ≤50 μm, and only discrete point-like β-(Al3Mg2) phases are generated in the matrix, without continuous network corrosion channels.

[0014] Compared with the prior art, the present invention can achieve the following technical effects: 1. The present invention adopts Sc-Zr-Mn-Cr composite microalloying, and a trace amount of scandium can achieve the dual effects of grain refinement and network β phase modification, solving the defects of high cost and limited corrosion resistance improvement of traditional single Sc modification; 2. 1. After the aluminum liquid is cooled, Al-Sc and Al-Zr master alloys are added to avoid the formation of coarse primary intermetallic compounds by Sc and Zr at high temperatures. Combined with low-speed stirring and precise ingot cooling rate, the problem of element segregation in industrial ingots is solved. 2. A gradient multi-pass rolling process is adopted, which includes high-temperature hot rolling, intermediate stress-relief annealing and moderate cold rolling. The deformation energy storage is controlled step by step. Combined with the grain-refining effect of nano-precipitates, the grain size is stably controlled within 50μm, taking into account both the plasticity and mechanical properties of the sheet. 3. Staged heat treatment avoids the continuous network β phase at the grain boundaries caused by traditional long-term high-temperature aging. Only discrete point β phases are precipitated, cutting off the continuous channel of intergranular corrosion and significantly reducing the sensitivity to intergranular corrosion and exfoliation corrosion. 4. The finished alloy meets both high mechanical properties and the harsh corrosion resistance requirements of marine environments. It fills the gap in the complete industrialization technology of modified aluminum-magnesium alloys and can be directly used in marine ship decks, lightweight aerospace structural components and coastal wind power equipment. The service life under salt spray and seawater conditions is increased by more than 2 times. The production process is compatible with existing aluminum processing production lines and has the value for large-scale industrialization. Detailed Implementation

[0016] The following will describe the implementation of the present invention in detail with reference to the embodiments, so that the process of how the present invention uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. Example 1

[0017] This embodiment provides a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, which, by mass percentage, comprises the following components: Mg: 5.2, Sc: 0.12, Zr: 0.08 (Sc / Zr = 1.5:1), Mn: 0.40, Cr: 0.03, Ti: 0.02, Fe: 0.10, Si: 0.08, with the balance being Al and unavoidable trace impurities, totaling ≤0.1% impurities.

[0018] This embodiment also provides a method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, which sequentially includes four major processes: aluminum molten metal melting and ingot casting, ingot homogenization annealing, gradient multi-pass rolling, and staged heat treatment. Specifically, it includes the following steps: (1) Smelting: After preheating the pure aluminum ingot to 720°C, put it into the smelting furnace and heat it to 755°C to completely melt it into aluminum liquid. Then, add Mg ingot, Al-Mn master alloy, Al-Cr master alloy and Al-Ti master alloy in sequence, stir and mix thoroughly, cool down to 730°C, add Al-Sc and Al-Zr master alloy, stir at low speed electromagnetically for 25 min, and keep it at the temperature for 30 min. (2) Casting: Semi-continuous casting is adopted, with online argon rotary degassing in the furnace and ceramic foam filtration purification. The cooling rate of the semi-continuous casting is controlled at 2.5℃ / s, and the casting speed is 70mm / min, to obtain a non-segregated alloy ingot. (3) Homogenization annealing: The cast ingot is kept at 440℃ for 12 hours and then air-cooled to room temperature; (4) Hot rolling: The homogenized ingot is subjected to multiple reciprocating hot rolling processes, and the deformation is gradually reduced. The initial rolling temperature is 420℃, the single-pass reduction is 15%, and the total hot rolling reduction is 78%, and the hot-rolled plate is obtained. (5) Intermediate stress-relief annealing: The obtained hot-rolled plate is annealed at 360℃ for 2 hours; (6) Cold rolling: The hot-rolled sheet is cold rolled at room temperature, and the total deformation of the cold rolling is controlled at 32% to obtain an aluminum alloy sheet with a thickness of 6mm. (7) Graded heat treatment: Solution quenching treatment, put the cold-rolled sheet into the solution furnace, set the temperature to 465℃, hold for 90 minutes, and immediately water quench after the holding is completed. The overall cooling rate is ≥100℃ / s to ensure that the alloy strengthening elements are fully dissolved. After quenching, the sheet is subjected to aging treatment, set the temperature to 320℃, hold for 6 hours, and then air cool to room temperature to obtain the finished aluminum alloy sheet.

[0019] Performance test results: Tensile strength: 426MPa; Yield strength: 273MPa; Elongation after fracture: 12.1%; Average grain size: 36μm; Al3(Sc,Zr) size: 8-18nm; Intergranular corrosion depth: 32μm; Exfoliation corrosion grade: EB. Example 2

[0020] This embodiment provides a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, which, by mass percentage, comprises the following components: Mg: 4.8, Sc: 0.096, Zr: 0.08 (Sc / Zr = 1.2:1), Mn: 0.30, Cr: 0.02, Ti: 0.01, Fe: 0.09, Si: 0.07, with the balance being Al and unavoidable trace impurities, totaling ≤0.1% impurities.

[0021] This embodiment also provides a method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, specifically including the following steps. (1) Smelting: After preheating the pure aluminum ingot to 720°C, put it into the smelting furnace and heat it to 755°C to completely melt it into aluminum liquid. Then, add Mg ingot, Al-Mn master alloy, Al-Cr master alloy and Al-Ti master alloy in sequence, stir and mix thoroughly, cool down to 710°C, add Al-Sc and Al-Zr master alloy, stir at low speed electromagnetically for 20 min, and keep it at the temperature for 25 min. (2) Casting: Semi-continuous casting is adopted, with online argon rotary degassing in the furnace and ceramic foam filtration purification. The cooling rate of the semi-continuous casting is controlled at 2.2℃ / s, and the casting speed is 60mm / min, to obtain a non-segregated alloy ingot. (3) Homogenization annealing: The cast ingot is kept at 430℃ for 10 hours and then air-cooled to room temperature; (4) Hot rolling: The homogenized ingot is subjected to multiple reciprocating hot rolling processes, and the deformation is gradually reduced. The initial rolling temperature is 410℃, and the total hot rolling reduction is 75%. The hot-rolled plate is obtained by rolling. (5) Intermediate stress-relief annealing: The obtained hot-rolled plate is annealed at 350℃ for 1.5h; (6) Cold rolling: The hot-rolled sheet is cold rolled at room temperature, and the total deformation of the cold rolling is controlled at 30% to obtain an aluminum alloy sheet with a thickness of 3mm. (7) Graded heat treatment: Solution quenching treatment, put the cold-rolled sheet into the solution furnace, set the temperature to 460℃, hold for 80 minutes, and immediately water quench after the holding is completed. The overall cooling rate is ≥100℃ / s to ensure that the alloy strengthening elements are fully dissolved. After quenching, the sheet is subjected to aging treatment, set the temperature to 310℃, hold for 5 hours, and then air cool to room temperature to obtain the finished aluminum alloy sheet.

[0022] Performance test results: Tensile strength: 403 MPa; Yield strength: 254 MPa; Elongation after fracture: 11.3%; Intergranular corrosion depth: 41 μm; Exfoliation corrosion rating: EB. Example 3

[0023] This embodiment provides a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, which, by mass percentage, comprises the following components: Mg: 5.6, Sc: 0.15, Zr: 0.075 (Sc / Zr = 2.0:1), Mn: 0.50, Cr: 0.04, Ti: 0.03, Fe: 0.11, Si: 0.09, with the balance being Al and unavoidable trace impurities, totaling ≤0.1% impurities.

[0024] This embodiment also provides a method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy, specifically including the following steps. (1) Smelting: After preheating the pure aluminum ingot to 720°C, put it into the smelting furnace and heat it to 760°C to completely melt it into aluminum liquid. Then, add Mg ingot, Al-Mn master alloy, Al-Cr master alloy and Al-Ti master alloy in sequence, stir and mix thoroughly, cool down to 720°C, add Al-Sc and Al-Zr master alloy, stir at low speed electromagnetically for 30 min, and keep it at the temperature for 35 min. (2) Casting: Semi-continuous casting is adopted, with online argon rotary degassing in the furnace and ceramic foam filtration purification. The cooling rate of the semi-continuous casting is controlled at 2.8℃ / s, and the casting speed is 80mm / min, to obtain a non-segregated alloy ingot. (3) Homogenization annealing: The cast ingot is kept at 450℃ for 14 hours and then air-cooled to room temperature; (4) Hot rolling: The homogenized ingot is subjected to multiple reciprocating hot rolling processes, and the deformation is gradually reduced. The initial rolling temperature is 410℃, the single-pass reduction is 12%, and the total hot rolling reduction is 80%, and the hot-rolled plate is obtained by rolling. (5) Intermediate stress-relief annealing: The obtained hot-rolled plate is annealed at 370℃ for 2.5h; (6) Cold rolling: The hot-rolled sheet is cold rolled at room temperature, and the total deformation of the cold rolling is controlled at 35% to obtain an aluminum alloy sheet with a thickness of 12mm. (7) Graded heat treatment: Solution quenching treatment, put the cold-rolled sheet into the solution furnace, set the temperature to 470℃, hold for 100min, and immediately water quench after the holding is completed. The overall cooling rate is ≥100℃ / s to ensure that the alloy strengthening elements are fully dissolved. After quenching, the sheet is subjected to aging treatment, set the temperature to 330℃, hold for 7h, and then air cool to room temperature to obtain the finished aluminum alloy sheet.

[0025] Performance test results: Tensile strength: 438MPa; Yield strength: 286MPa; Elongation after fracture: 10.2%; Intergranular corrosion depth: 45μm; Exfoliation corrosion grade: EA.

[0026] The foregoing description illustrates and describes several preferred embodiments of the present invention. However, as previously stated, it should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the inventive concept described herein through the foregoing teachings or techniques or knowledge in related fields. Any modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A trace scandium-regulated corrosion-resistant aluminum-magnesium alloy, characterized in that: By mass percentage, it comprises the following components: Mg: 4.8–5.6%, Sc: 0.08–0.15%, Mn: 0.3–0.5%, Zr: 0.05–0.10%, Cr: 0.02–0.04%, Ti: 0.01–0.03%, Fe ≤ 0.12%, Si ≤ 0.10%, with the balance being Al and unavoidable trace impurities, totaling ≤ 0.1% impurities.

2. The trace scandium-regulated corrosion-resistant aluminum-magnesium alloy according to claim 1, characterized in that: The mass ratio of Sc to Zr is controlled as (1.2~2.0):

1.

3. The trace scandium-regulated corrosion-resistant aluminum-magnesium alloy according to claim 1, characterized in that: The finished aluminum alloy has a tensile strength ≥400MPa, a yield strength ≥250MPa, an elongation after fracture ≥10%, and corrosion resistance that meets the requirement of intergranular corrosion depth ≤50μm and exfoliation corrosion level EA~EB.

4. The trace scandium-regulated corrosion-resistant aluminum-magnesium alloy according to claim 1, characterized in that: The aluminum alloy is used in marine ship structural components, lightweight load-bearing components for aerospace, and corrosion-resistant plates for coastal wind power equipment.

5. A method for preparing a trace scandium-regulated corrosion-resistant aluminum-magnesium alloy, characterized in that: Specifically, it includes the following steps: (1) Smelting: After preheating the pure aluminum ingot to 720°C, put it into the smelting furnace and heat it to 750-760°C to completely melt it into aluminum liquid. Then, add Mg ingot, Al-Mn master alloy, Al-Cr master alloy and Al-Ti master alloy in sequence, stir and mix thoroughly, then adjust the temperature of the aluminum liquid to 700-730°C, add Al-Sc and Al-Zr master alloy, stir at low speed electromagnetically for 20-30 min, and keep it at the temperature for 25-35 min. (2) Casting: Semi-continuous casting is adopted, with online argon rotary degassing and ceramic foam filtration purification in the furnace. The cooling rate of the semi-continuous casting is controlled at 2.2~2.8℃ / s, and the casting speed is 60mm / min~80mm / min, to obtain a non-segregated alloy ingot. (3) Homogenization annealing: The cast ingot is kept at 430-450℃ for 10-14 hours and then air-cooled to room temperature; (4) Hot rolling: The homogenized ingot is subjected to multiple reciprocating hot rolling processes, and the deformation is gradually reduced. The initial rolling temperature is 410-430℃, the single-pass reduction is 12%-18%, and the total hot rolling reduction is 75%-80%. The hot-rolled plate is obtained by rolling. (5) Intermediate stress-relief annealing: The obtained hot-rolled plate is kept at 350-370℃ for 1.5-2.5h; (6) Cold rolling: The hot-rolled sheet is cold rolled at room temperature, and the total deformation of the cold rolling is controlled at 30% to 35% to obtain aluminum alloy sheet with a thickness of 1.5 to 12 mm. (7) Graded heat treatment: The obtained aluminum alloy plates are subjected to solution quenching and low temperature aging treatment in sequence.

6. The method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy according to claim 5, characterized in that: The solution quenching process involves placing the cold-rolled sheet in a solution furnace, setting the temperature to 460–470°C, holding it for 80–100 minutes, and immediately water quenching it after the holding period, with an overall cooling rate ≥100°C / s, to ensure that the alloy strengthening elements are fully dissolved.

7. The method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy according to claim 5, characterized in that: The low-temperature aging treatment involves aging the quenched sheet material at a temperature of 310–330°C for 5–7 hours, followed by natural air cooling to room temperature, resulting in the finished aluminum alloy sheet material.

8. The method for preparing a trace scandium-controlled corrosion-resistant aluminum-magnesium alloy according to claim 5, characterized in that: After solution treatment and aging, the size of Al3(Sc,Zr) precipitates inside the alloy is controlled within 5–25 nm, and the average grain size of the plate is ≤50 μm.

Citation Information

Patent Citations

  • Al-Mg-Sc-Zr aluminum alloy plate and manufacturing method thereof

    CN104694801A